Single-layer graphene membranes by crack-free transfer for gas mixture separation - Shiqi Huang (Nature Portfolio, 2018)
Graphene shows great promise for gas separation applications, but obtaining large membranes that are free of cracks and tears remains highly challenging. Here, the authors realize monolayer, crack-free, millimeter-scale graphene membranes that exhibit selective gas permeation solely thanks to their intrinsic defects